Implementasi Sistem Kontrol dan Monitoring pH pada Tanaman Kentang Aeroponik secara Wireless - Andrika Wahyu Wicaksono; Edita Rosana Widasari; Fitri Utaminingrum (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The needs of potato each year has increased, but not offset by increased production and land area for commodity crops of potatoes. To boost production in an increasingly limited land, aeroponics techniques into one solution for farmers who have no land availability. Aeroponics potato production techniques have yields more good than conventional techniques and with the land. PH is one of the elements that greatly affect the growth of aeroponic plant. The ideal pH range for an aeroponics system ranges between 5.5-6.5. Then the system control and monitoring is required in an aeroponics techniques. In this research for controlling and monitoring the State of a pH using wireless transmission. There are six nodes that is two nodes, one node sensor Coordinator, and three nodes of the actuators. From the test results obtained by the sensor data reading of pH value of 1% error within an error reading of 0.08 degree pH. Sensor data transmission using wireless data on delivery without hitch has the accuracy of data delivery of 99.98% with one node of the sensors and 96.13% with two sensor nodes. On delivery with the hitch has the level of accuracy of the data delivery of 99.93% with one sensor nodes and of 92.99% with two sensor nodes